Parker [videorecording (DVD)] - Hackford, Taylor, 1944-; Statham, Jason, 1967-; Lopez, Jennifer, 1970-; Chiklis, Michael, 1963-; Stark, Richard, 1933-2008 (Sony Pictures Home Entertainment, 2013)
Parker is a thief who has an unusual code. He doesn't steal from the poor or hurt innocent people. He is asked to join four other guys, one of whom is related to a known mobster. They pull off the job flawlessly and Parker wants to part ways with them. When he refuses to join them for another job, they try to kill him. They dispose of his body, but someone finds him...still alive. After recovering, he sets out to get back at the ones who tried to kill him, another one of his codes.